Screening and genomic evaluation of keratinolytic protease producing Chryseobacterium sp. from tannery waste and its potential application in dehairing of goat skin - Taslima Akter; Murshed Hasan Sarkar; Shashanka Shekhar Sarker; Nourin Tarannum; Showti Raheel Naser; Sanjana Fatema Chowdhury; Sahana Parveen (Journal of Genetic Engineering and Biotechnology)
Lime and Na2S, used in dehairing in the tannery industry, cause the generation of toxic wastes. Ecological security and financial issues demand a look for innovative approaches to leather dehairing free from pollution. The primary goal of this investigation was to explore keratinolytic protease producing bacteria from tannery waste, their genomic evaluation and to assess their possible use in the dehairing process. A newly isolated Gram-negative bacterium (LRI-TA6) was characterized and checked for its keratinolytic protease producing ability. The strain was identified as Chryseobacterium cucumeris through whole genome sequencing. The genome was 4,541,898 bp in size and contain 4,426 protein coding sequences (CDS) with 36.38 % of GC content. Twenty-five open reading frames (CDS) were found as protease producing genes notably DegQ (serine protease), DegS, and ATP-dependent protease DP (EC 3.4.21.-). The isolate revealed enzyme production throughout an extended pH range of 5.0 to 8.0, and a broad temperature range of 10 °C to 38 °C. The isolate LRI-TA6 was sensitive to all five antibiotics (amoxicillin, tetracycline, gentamicin, ciprofloxacin, and vancomycin) with zone diameter ranges from 17.2 ± 0.8 to 32 ± 0.0 mm. The enzyme was shown to have 29.9 ± 6.7 and 83.6 ± 0.2 U/ml of keratinolytic and proteolytic activity, respectively. By employing crude keratinase, the removal of hair from goat skin was accomplished in 18 h. This study is the first report to isolate and characterize C. cucumeris from tannery waste and also the amazing 18 h dehairing capabilities and thus might be utilized for further studies towards commercial synthesis of keratinase for use in leather processing sectors.